Digital evolution of business models in the financial sector: from traditional banks to platform ecosystems (Economics and region, 2025)
This article explores the specifics of digital transformation and the unique characteristics of new financial sector models amidst a slowdown in financial resource acquisition and heightened competitive pressures. It examines the shifts in the organizational and institutional framework of financial service provision, driven by innovative technologies, digital changes, and quantitative easing monetary policy. The evolution of banking activities, the emergence of FinTech companies, and cross-sector competition from BigTech and other non-banking players are analyzed. Particular attention is paid to emerging business models such as open banking, embedded finance, and platform ecosystems, which are disrupting traditional banking paradigms.Two types of platforms are discussed: transactional (exchange platforms) and development (product platforms), as well as ecosystems formed through partnerships and collaborations. The importance of banks transitioning from vertically integrated value chains to network-based platform interactions is emphasized, outlining three strategic options: digitizing individual processes, connecting to other platform ecosystems as a BaaS provider, and establishing their own online platform.The article also analyzes seven distinct ecosystem business models: symbiotic, marketplace, scaling, augmentation, cooperation, value chain, and integrator, along with strategies for transitioning to digital platform ecosystem-based financial service provision. The features of each model and examples of their application across various industries, including finance, are explored. It is concluded that effective distribution of economic value among platform participants and the formation of a partner interaction network are essential for the long-term success of a platform ecosystem. Special emphasis is placed on the importance of addressing customer needs and creating a unique value proposition. Banks must assess the full spectrum of customer needs (both financial and non-financial) and invest in solutions that meet critical requirements, ensuring a high level of personalization and ease of service use.
Keywords: digital transformation; financial sector; digitalization; business models; fintech; ecosystems; open banking; embedded finance; competition; financial services; transaction platforms; platform development; value chain; BaaS; network economy